MODELS OF AGROTOURISM DEVELOPMENT APPROACH CONSUMER BEHAVIOR ON CAMPUS UPN “VETERAN” EAST JAVA - Hadi Suhardjono; Nora Augustien; Pangesti Nugrahani; Liastyn Dwika Putri (UPT Penerbitan Universitas Jember, 2017)
The use of planting media in a nursery, is crucial to the growing rate of seedlings. Plantingvegetable crops, becoming faster growing with its loose planting media, adequate nutritionand moisture are assured. Physically organic material in the form of compost straw, cocopeat,and corn leaves with indigenous technology capable of crumb soil medium so that the growthof seedling become assured. One factor study was the composition of growth media preparedin Completely Randomized Design (RAL) with 8 treatments and repeated 3 (three) times.Type of treatment as follows: P0 = Soil; P1 = Soil and Urea; P2 = Soil and Compost (2: 1); P3 =Soil, Compost and Cocopeat (2: 1: 1); P4 = Soil, Compost and Straw (2: 1: 1); P5 = Soil,Compost and Corn Leaves (2: 1: 1); P6 = Soil, Compost, Corn and Straw Leaves (2: 1: 1: 1); P7= Soil, Compost, Corn Leaf, Straw and Cocopeat (2: 1: 1: 1: 1). The results showed that thepercentage of seed germination at 5-7 days had reached 88% - 95%, germination rate of 4.53- 4,63 days by using composting medium of straw, cocopeat and maize leaf. The reduction ofsoil media is not significantly different from the use of soil alone or the use of urea + soil. Inthe length parameter of the plant, the number of leaves, leaf area and wet weight of the plantsdid not differ significantly between treatments, tended to be high at P4. P4 medium was ableto increase wet weight of seeds of mustard 53% and 38% compared to medium P0 (soil) andP1 (soil + urea)